Pengaruh Penggunaan Teks Berwarna terhadap Hasil Belajar Siswa Ditinjau dari Gaya Belajar - Aditya Juliant; Zainal Abidin; Kurnia Noviartati (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2020)
The aim of this study determined (1) the effect of using color text towards the learning outcome on the topic matrices operation and (2) the comparison of mean using color text of visual, auditory, and kinesthetic learning style. This research is an experiment research with Pretest-Posttest Control Group Design. Test and questionnaire are used as instrument in this research. The test is used to investigate the learning outcome before and after treatment. Questionnaire is used to investigate the learning styles level and anxiety in learning by using color text. The technique of data analysis applied is t-test and One Way Anova. The result of this research showed that there is an effect of using color text in the learning outcome on the topic matrices operation. Analysis of t-test shows that is 2,46 with significant level of 5% and is 2,01. The result showed (t-value is bigger than t-table). In conclusion, there is an effect of using color text in the learning outcome on the topic matrices operation. For knowing comparison mean visual, auditory, and kinesthetetic is used One-Way ANOVA test, showed that is 0,109 and is 5,143. The result showed that (f_value is bigger than f_table). In the conclusion, learning outcome in 3 students with different learning styles from the experiment class do not significantly different regarding to the comparison mean value.